Correlation between the neonatal EEG and the neurological examination in the first year of life in infants with bacterial meningitis Correlación entre el EEG neonatal y el examen neurológico en el primer año de vida en recién nacidos con meningitis bacteriana - Adrián Poblano; Roberto Gutiérrez (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To assess the contribution of neonatal electroencephalogram (EEG) and its correlation with the neurological examination at age of 9 months in newborns with bacterial neonatal meningitis. METHOD: Twenty seven infants were studied with positive cerebrospinal fluid (CSF) culture for bacteria. We used the worse EEG result during acute phase of meningitis, and performed neurologic follow-up after discharge from hospital. Background cerebral activity was classified as normal or mildly, moderately, or markedly abnormal. Neurologic examination outcomes was classified normal, mild abnormalities, moderate abnormalities and severe abnormalities. RESULTS: EEG performed in the neonatal period during acute bacterial meningitis predicts adverse outcome early at age of 9 months, and had a significant correlation with cephalic perimeter and active tone alterations. CONCLUSION: Neonatal EEG is useful for predicting abnormal outcomes, especially cephalic perimeter and active tone abnormalities at 9 months of age in infants with bacterial neonatal meningitis. OBJETIVO: Medir la contribución del electroencefalograma (EEG) neonatal y su correlación con el examen neurológico a la edad de 9 meses en recién nacidos con meningitis neonatal bacteriana. MÉTODO: Se estudió a 27 neonatos con cultivos positivos de líquido cefalorraquídeo a bacterias. Se uso el peor resultado del EEG obtenido durante el periodo agudo de la meningitis. El seguimiento neurológico se efectuó tras el egreso hospitalario. La actividad de fondo del EEG se clasificó en normal y anormal leve, moderada y severa. El examen neurológico se clasificó en normal, y anormal leve moderado y severo. RESULTADOS: El EEG realizado durante el periodo neonatal durante la fase aguda de la meningitis bacteriana predice bien un resultado adverso a la edad de 9 meses, con correlaciones significativas con el perímetro cefálico y con las alteraciones del tono activo. CONCLUSION: El EEG neonatal es útil para predecir anormalidades del neurodesarrollo especialmente en el perímetro cefálico y anormalidades del tono durante el primer año de vida en niños que tuvieron meningitis neonatal bacteriana.